Effect of Various Concentrations of IBA and NAA on the Rooting of Stem Cuttings of Mulberry (Morus Alba L.) under Mist House Condition in Garhwal Hill Region - SINGH, K.K.; CHOUDHARY, T.; KUMAR, A. (Indian Journal of Hill Farming, 2015)
Stem cuttings of Morus alba were treated with 1000, 1500 and 2000 mg.L-1 IBA and NAA solutions by quick dip method. These cuttings were rooted in a rooting media of 1:1 mixture of sandy soil and farm yard manure in plastic root trainers inside a mist house. Among all the treatments, number of sprouted cuttings, length of the roots/cutting, percentage of rooted cutting, lengths of longest sprouts of root were higher in IBA 2000 mg.L-1.